Internationalisation at Home: The Cases of the Universities of Makerere and Nairobi - Opeto, Bonny; Onen, David (International Journal of African Higher Education, 2024)
This article presents a comparative analysis of internationalisation efforts at Makerere University in Uganda and the University of Nairobi in Kenya, with a focus on internationalisation at home (IaH). It examines various aspects of IaH, including institutional commitment, policies, leadership, curriculum, funding, student enrolment and collaborative networks. Motivated by concerns about the limited internationalisation initiatives in East African universities, these universities were selected as case studies due to their historical ties and flagship status in their countries. Utilising documentary analysis and literature review methodologies, data were collected from policy documents, statistical records and updates from the universities’ websites and relevant educational bodies. The study found that both institutions have made notable progress in internationalising their environments through IaH, although the extent varies. The findings reveal comparable efforts but highlight the need for enhanced institutional commitment, improved policies, strengthened leadership, innovative curricula, optimal funding, diverse enrolment strategies and robust partnerships to advance IaH and overall internationalisation in East African higher education.